A Remote Power Management Strategy for the Solar Energy Powered Bicycle - Chung-Hsing Chao (Universitas Ahmad Dahlan, 2011)
In this paper, a solar energy powered bicycle by a wireless sensor network (WSN) far-end network monitoring solar energy to transfer the electrical energy storage and the effectiveness analysis is proposed. In order to achieve this goal, an embarked ZigBee by a solar-powered bicycle the far-end wireless network supervisory system is setup. Experimental results prove that our prototype, the solar energy powered bicycle, can manage the solar energy for charging two Lead-Acid batteries pack. As a result, the user by the wireless network in parking period knows the data on the amount of immediate solar radiation, the degree of illumination, the ambient temperature, and electrical energy storage capacity information by the internet interface.